1980
DOI: 10.1016/s0006-3495(80)85010-7
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular conformation in solution. Study of carbonic anhydrase by the positron annihilation technique

Abstract: The structural features of carbonic anhydrase (carbonate hydro-lyase; EC 4.2.1.1) in aqueous solution were probed by the positron annihilation technique. The data obtained under varying conditions of temperature, pH, and enzyme concentration were interpreted in terms of the free volume model. The change of enzymic activity with temperature is accompanied by a change in free volume of the protein. Upon thermal denaturation an irreversible change in free volume of the molecule occurred. At low temperatures the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, he focused his attention on the order and arrangement of tissue water and not on muscle structure. Further studies on complex biological systems like biological membranes or proteins moved positronium research towards structural biology and showed that this approach was efficient in the study of biological reactions (such as electron transfer (Jean and Ache, 1977)), phase transition of lipids (Chow et al, 1981;Jean and Hancock, 1982;Stinson et al, 1980) macromolecule structure (Handel et al, 1976), hydratation (Akiyama et al, 2007Gregory et al, 1992;Handel et al, 1980) and porosity (Chamerski et al, 2017;Pamula et al, 2006) of biological samples. Nowadays, after many years of focused research, PALS appears to be a promising technique in the investigation of the structure of macromolecules (Chen et al, 2012) and clinical samples (Avachat et al, 2022;Moskal et al, 2021a,b;Zgardzinska et al, 2020).…”
Section: Development Of Positronium Research In Biology and Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…However, he focused his attention on the order and arrangement of tissue water and not on muscle structure. Further studies on complex biological systems like biological membranes or proteins moved positronium research towards structural biology and showed that this approach was efficient in the study of biological reactions (such as electron transfer (Jean and Ache, 1977)), phase transition of lipids (Chow et al, 1981;Jean and Hancock, 1982;Stinson et al, 1980) macromolecule structure (Handel et al, 1976), hydratation (Akiyama et al, 2007Gregory et al, 1992;Handel et al, 1980) and porosity (Chamerski et al, 2017;Pamula et al, 2006) of biological samples. Nowadays, after many years of focused research, PALS appears to be a promising technique in the investigation of the structure of macromolecules (Chen et al, 2012) and clinical samples (Avachat et al, 2022;Moskal et al, 2021a,b;Zgardzinska et al, 2020).…”
Section: Development Of Positronium Research In Biology and Medicinementioning
confidence: 99%
“…The first applications of positronium properties in the life sciences were made by Handel in late 70s (Handel et al, 1976(Handel et al, , 1980. Having in mind that positron annihilation lifetime is sensitive to changes in free volume caused by pressure (which is rarely studied in biological systems) or by thermal expansion in the same phase, he showed significant changes in positronium lifetime during phase transitions of biological systems.…”
Section: A Positronium In Biological Materials and Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural changes, as associated with their free volume, in membranes have been studied as a function of nitrous oxide, along with conformational changes in Na + /K + -ATPase in the membranes upon ATP and Mg 2+ binding [70]. Temperature dependence of positron lifetimes was determined for hydrated bovine carbonic anhydrase [71,72]. In addition, positron annihilation techniques were applied to the determination of the complex formation constants for a series of molecular complexes of vitamin K1 or tocopherolquinone with donors such as mono-, di-, and tri-n-butylamines, indole, and vitamin D3 in cyclohexane or benzene solutions [73].…”
Section: Pas In Biomolecular Systemsmentioning
confidence: 99%